Impact of left ventricular end-diastolic pressure on clinical outcomes in patients with ST-elevation myocardial infarction (Hunter LVEDP Study): a prospective, single-centre study - John Attia; Nicholas Collins; Mohammed S Al-Omary; Andrew J Boyle; Max Ray; Arshad A Khan; Trent Williams; Jonah Taylor (BMJ Open)
Objectives Elevated left ventricular end-diastolic pressure (LVEDP) in ST-segment elevation myocardial infarction (STEMI) has been studied in patients who received thrombolysis or who were treated early in the primary percutaneous coronary intervention (PCI) era; LVEDP was found to be a predictor of adverse outcomes in these retrospective post hoc analyses. The aim of the current analysis is to assess the prognostic value of the elevated LVEDP in STEMI patients undergoing primary PCI in current contemporary practice.Design Prospective, single-centre study.Participants Our study enrolled STEMI patients with elevated LVEDP undergoing primary PCI at John Hunter Hospital, Newcastle, Australia.Primary outcome measure The primary endpoint was the combination of 12-month all-cause mortality and heart failure admissions, comparing different quartiles of LVEDP.Results A total of 997 patients underwent primary PCI at our hospital during the 5-year study period (age: 64±13 years, males: 73%; n=728) from 1 January 2015 to 31 December 2019. The median LVEDP for the whole cohort was 27 mm Hg (IQR: 22–31 mm Hg). The median LVEDP was 17 mm Hg (IQR: 13–18 mm Hg) and 33 mm Hg (IQR: 30–36 mm Hg) for 1st and 4th quartiles respectively (p<0.01). At 1 year, the composite endpoint of all-cause mortality or heart failure admission was 12% vs 26% (p=0.01) in quartiles 1 and 4 respectively. The mean left ventricular ejection fraction (LVEF) for the whole cohort was 50%. In multivariate regression analysis, age, anterior STEMI, out of hospital cardiac arrest and LVEDP quartile 4 were independent predictors of mortality; LVEF was not.Conclusions LVEDP is an independent predictor of adverse outcomes in STEMI patients, despite a relatively normal LVEF. Further prospective studies are needed to assess the effects of early reduction in LVEDP on the prognosis.